2014
DOI: 10.1039/c4ta00070f
|View full text |Cite
|
Sign up to set email alerts
|

Star-shaped Pd@Pt core–shell catalysts supported on reduced graphene oxide with superior electrocatalytic performance

Abstract: A surfactantless, one-pot reduction approach for Pd@Pt core–shell nano-stars on reduced graphene oxide with enhanced catalytic activity and stability for methanol oxidation in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 78 publications
5
88
0
Order By: Relevance
“…[20][21][22][23] For instance, Youngmin Kim et al have prepared star-shaped core-shell PdPt nanoparticles on graphene sheets via a one-pot synthetic route, which presented a great improvement in the electrocatalytic performance towards the methanol oxidation reaction. 24 Yizhong Lu et al have reported a novel one-step synthetic strategy for the in situ synthesis of concave PtPd nanocubes on reduced GO nanosheets, which exhibited enhanced electrocatalytic activity and high durability toward methanol oxidation. 25 Herein, we report a facile synthesis of RGO-supported PdNi nanowire networks, using Ni as a template material with the assistance of a small amount of trisodium citrate at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] For instance, Youngmin Kim et al have prepared star-shaped core-shell PdPt nanoparticles on graphene sheets via a one-pot synthetic route, which presented a great improvement in the electrocatalytic performance towards the methanol oxidation reaction. 24 Yizhong Lu et al have reported a novel one-step synthetic strategy for the in situ synthesis of concave PtPd nanocubes on reduced GO nanosheets, which exhibited enhanced electrocatalytic activity and high durability toward methanol oxidation. 25 Herein, we report a facile synthesis of RGO-supported PdNi nanowire networks, using Ni as a template material with the assistance of a small amount of trisodium citrate at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…EXAFS is able to reveal short-range structural motifs responsible for catalyst activity enhancements, such as core-shell structures with surface reactivity modified by strain and ligand effects. [17][18][19] This has been shown in multiple examples of ORR catalysts for low-temperature fuel cell systems, where Pd has been used extensively as a promoter of Pt activity for the oxygen reduction reaction, [20][21][22][23][24][25] often in a Pd-core/Pt-shell morphology. Based on particle sizes derived from the XRD data, we stipulate that the catalyst particles are large enough to be nearly fully coordinated (N = 12 for fcc materials) .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, graphene and its derivatives, as a kind of ideal carbonbased supports, have attracted considerable scientific interest. This is attributed to their excellent mechanical, electrical, and thermal properties, as well as their high specific surface area [23]. For example, Li and coworkers developed a one-pot strategy for the preparation of hierarchical dendritic garland-like PtPd nanostructures supported on reduced graphene oxide with significantly enhanced electrocatalytic activity and better stability toward methanol and ethanol oxidation in alkaline media [24].…”
Section: Introductionmentioning
confidence: 99%